Laowomaru: Kisah Samson Dari Pulau Nias sebagai Inspirasi Penciptaan Tari Kontemporer - Hulu, Ijes Jenifes; Astuti, Andi Arie; Mayangsari, Marrisa Aulia (FKIP, Universitas Palangka Raya, 2025)
The creation of the dance artwork raises the Laowomaru dance because the author wants to reintroduce the legendary story of the Nias tribe, so that the existing cultural values will not be lost. This work also conveys messages and motivation to the audience. Therefore, the author created a new contemporary dance piece to enable free movement with creativity according to the author’s abilities. The method used in this dance work employs Hawkins' creation theory, which is known in the context of art to emphasize that art creation involves several main stages, namely: Exploration, Improvisation, and Formation. The Laowomaru dance project: The Story of Samson from Nias Island aims to create a contemporary dance that visualizes the character of Laowomaru and introduces the legend to the younger generation while still being grounded in tradition. This dance benefits cultural preservation, introduces the Nias warrior figure, and serves as inspiration for other choreographers. The work was developed through the stages of exploration, improvisation, and formation based on Hawkins' dance creation theory, and analyzed using La Meri’s theory. There are 10 dancers from the students and university students of Palangka Raya. This dance uses 52 floor patterns, digital music with a duration of 12 minutes and 17 seconds, as well as costumes and makeup that reflect the cultural identity of Nias.